STUDY OF ANTIOXIDANT CAPACITY OF BLACK ELDER BERRIES ANTHOCYANINS USING THE METHOD OF COMPUTER CHEMISTRY - Стеценко, Наталія; Гойко, Ірина; Башта, Алла (Modern engineering and innovative technologies, 2023)
The paper analyzes the spatial and electronic structure of the anthocyanins of black elderberry fruits, cyanidin-3-0-glucoside and cyanidin-3-sambubioside, in order to determine their antioxidant capacity in comparison with quercetin. Calculations were p